Civil Reserve Component as an Alternative for Strengthening Border Security in Indonesia - Ayuni, Qurrata (Indonesian Journal of International Law, 2018)
Indonesia as the world’s largest archipelagic state has 90 outer islands with 67 islands bordering to the neighboring countries. Through this frontier, it is found number of problems that arise such as the smuggling of goods and people, drug trafficking, terrorism, small arms smuggling and occupation of territory by neighbouring countries. Not all these problems can be handled by the government and Indonesia National Army (Tentara Nasional Indonesia or TNI). Therefore the idea for the establishment of civil reserve components through basic military training to increase border community defence of Indonesian sovereignty needs to be considered. Through the civil reserve component, the community will be given training to strengthen Pancasila values while preparing the community to be responsive to the various border issues. Using a juridical normative study, this paper will discuss the benefits and challenges of border security through the strengthening of the civil reserve component using national law and international law perspectives